Rogelio Bermejo Ortega and challenge of primary Health care in Peru - Bustíos, Carlos (2023)
The publication of this historiographical article has two objectives: The first is to pay tribute to the life trajectory of the sanfernandino doctor Rogelio Bermejo Ortega, one of the Peruvian pioneers of rural health, of community participation and intersectoral work in the development of general welfare. The second, to carry out from his life trajectory a first critical analysis of the implementation process of Primary Health Care (PHC) in Peru, based on the observations stated in his work “Primary Health Care in Peru”. Rescuing some elements to sustain —in these years of general crisis— a reform of the health system, oriented in an authentic way to the achievement of “health for all and per all” in Peru.